2020
DOI: 10.1002/jmri.27458
|View full text |Cite
|
Sign up to set email alerts
|

Comparison Between Diffusion‐Weighted MRI and 123I‐mIBG Uptake in Primary High‐Risk Neuroblastoma

Abstract: Background High‐risk neuroblastoma (HR‐NB) has a variable response to preoperative chemotherapy. It is not possible to differentiate viable vs. nonviable residual tumor before surgery. Purpose To explore the association between apparent diffusion coefficient (ADC) values from diffusion‐weighted magnetic resonance imaging (DW‐MRI), 123I‐meta‐iodobenzyl‐guanidine (123I‐mIBG) uptake, and histology before and after chemotherapy. Study Type Retrospective. Subjects Forty patients with HR‐NB. Field Strength/Sequence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…Diffusion imaging may also be useful in detecting small metastases in solid viscera, especially the liver. [10][11][12] Currently, WB-MRI, a noninvasive imaging method, can be used to diagnose and stage tumors, as well as to assess therapeutic responses in pediatric solid tumors and lymphomas. 4,5 The availability of studies on the role of WB-MRI in neuroblastoma is still limited.…”
Section: Discussionmentioning
confidence: 99%
“…Diffusion imaging may also be useful in detecting small metastases in solid viscera, especially the liver. [10][11][12] Currently, WB-MRI, a noninvasive imaging method, can be used to diagnose and stage tumors, as well as to assess therapeutic responses in pediatric solid tumors and lymphomas. 4,5 The availability of studies on the role of WB-MRI in neuroblastoma is still limited.…”
Section: Discussionmentioning
confidence: 99%
“…Other non-nuclear imaging biomarkers should not be overlooked, such as recent advancements with MRI diffusion weighted imaging MRI (MRI-DWI). Apparent diffusion coefficients with MRI-DWI have been associated with significant post-chemotherapy tumour reductions where [ 123 I]mIBG had no significant association [103]. While these studies have not yet been applied to [ 131 I]mIBG MRT, the association between diffusion and effective delivery of MRT agents such as [ 177 Lu]Lu-DOTATATE have been found preclinically [104,105].…”
Section: Challenges In Establishing Cohort Based Alara Thresholds Wit...mentioning
confidence: 99%
“…[ 8 22 ] mIBG avidity of the primary tumor does not correlate with restricted diffusion at diffusion-weighted MRI (DW-MRI). [ 23 ]…”
Section: I-meta-iodobenzylguanidine Single-photon Emission Computerised Tomography/computerized Tomography Scan At Diagnosismentioning
confidence: 99%
“…[ 24 ] In this context 123 I-mIBG SPECT/CT often shows heterogeneous mIBG avidity within the primary tumor mass: nodules of viable tumor on MRI can exhibit a high, moderate, low or absent mIBG avidity on SPECT/CT. [ 23 ] This is relevant when molecular radiotherapy with 131 I-mIBG is contemplated: given the different degree of mIBG avidity (or no avidity at all), the uptake of the therapeutic radiopharmaceutical within the neuroblastoma lesions will be higher or lower, or completely absent, with more or less or no response. [ 25 ] Initial attempts at testing the avidity of the primary neuroblastoma to different imaging biomarkers (in particular, 123 I-mIBG targeting NE analog re-uptake, and 68 Ga-DOTATATE targeting somatostatin receptors) have shown that some neuroblastoma cells show avidity for one tracer and not for the other, and vice versa: this finding needs further evaluation as it may have implications for molecular radiotherapy in that two combined therapeutic radiopharmaceuticals (for example, 131 I-mIBG and 177 L u-DOTATATE) may potentially yield a better response than one.…”
Section: I-meta-iodobenzylguanidine Single-photon Emission Computerised Tomography/computerized Tomography Scan At Diagnosismentioning
confidence: 99%
See 1 more Smart Citation